Normalization of tumor vessels by Tie2 activation and Ang2 inhibition enhances drug delivery and produces a favorable tumor microenvironment - Park, Jin-Sung; Augustin, Hellmut (Cancer cell, 2016)
A destabilized tumor vasculature leads to limited drug delivery, hypoxia, detrimental tumor microenvironment, and even metastasis. We performed a side-by-side comparison of ABTAA (Ang2-Binding and Tie2-Activating Antibody) and ABA (Ang2-Blocking Antibody) in mice with orthotopically implanted glioma, with subcutaneously implanted Lewis lung carcinoma, and with spontaneous mammary cancer. We found that Tie2 activation induced tumor vascular normalization, leading to enhanced blood perfusion and chemotherapeutic drug delivery, markedly lessened lactate acidosis, and reduced tumor growth and metastasis. Moreover, ABTAA favorably altered the immune cell profile within tumors. Together, our findings establish that simultaneous Tie2 activation and Ang2 inhibition form a powerful therapeutic strategy to elicit a favorable tumor microenvironment and enhanced delivery of a chemotherapeutic agent into tumors.
Gesehen am 31.10.2019